1973
DOI: 10.1042/bj1320717
|View full text |Cite
|
Sign up to set email alerts
|

The oxoacyl-coenzyme A thiolases of animal tissues

Abstract: 1. The activities and relative 3-oxoacyl-CoA substrate specificities of oxoacyl-CoA thiolase were determined in a large number of animal tissues. The relative activities with different 3-oxoacyl-CoA substrates varied widely in different tissues and, in addition, the activity as measured with acetoacetyl-CoA (but not with other longer-carbon-chain acyl-CoA substrates) was activated by K(+). 2. These properties were due to the presence, in different proportions in each tissue, of three classes of thiolase, all o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
157
0
1

Year Published

1973
1973
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(167 citation statements)
references
References 19 publications
9
157
0
1
Order By: Relevance
“…Rat liver thiolases have been separated by DEAEcellulose and phosphocellulose column chromatography [1,20]. By this separation procedure with use of acetoacetyl-CoA and 3-oxooctanoyl-CoA as the substrates, it was revealed that a novel thiolase was markedly increased in the livers of rats when fed with the di(2-ethylhexy1)phthalate-containing diet.…”
Section: Discussionmentioning
confidence: 99%
“…Rat liver thiolases have been separated by DEAEcellulose and phosphocellulose column chromatography [1,20]. By this separation procedure with use of acetoacetyl-CoA and 3-oxooctanoyl-CoA as the substrates, it was revealed that a novel thiolase was markedly increased in the livers of rats when fed with the di(2-ethylhexy1)phthalate-containing diet.…”
Section: Discussionmentioning
confidence: 99%
“…The buffer anion used was sulphate rather than chloride as monovalent anions inhibit the enzyme [2]. The extinction coefficient of acetoacetyl-CoA under these conditions is 16.9 X103 litre.mo1-1 [9].…”
Section: North-holland Publishing Company -Amsterdammentioning
confidence: 99%
“…Asterisks indicate the occurrence of substrate inhibition. reported before by others for cTh [1,3]. These similarities in chromatographic behaviour as well as the low activity of pTh in whole peroxisomes in comparison to the activities of the known peroxisomal thiolases suggested that we might have purified a contaminant cytosolic acetoacetyl-CoA thiolase from the peroxisomal fraction.…”
Section: Comparison Of the Properties Of The Acetoacetyl-coa Thiolasementioning
confidence: 73%
“…Acetoacetyl-CoA thiolases catalyse the following reversible reaction: acetoacetyl ÿ CoA 1 CoA Y 2 acetyl ÿ CoA and do not react with medium and long chain 3-oxoacyl-CoAs. In the liver the enzymes mediate mainly acetoacetyl-CoA formation, whereas in extrahepatic tissues the mitochondrial reaction proceeds in the direction of acetyl-CoA synthesis [1,7,8].…”
mentioning
confidence: 99%
See 1 more Smart Citation